Smoke Repellent Action of Eicosatrienoic Acid from Gliricidia sepium against Filarial Vector Mosquitoes: An Experimental Study - Thomas, Jiji; Govindan, M. Shonima; Kurup, G. Muraleedhara (New Visions in Biological Science Vol. 7, 2021)
Mosquito-borne infections are still a leading source of illness and death. Use of synthetic insecticides to control mosquitoes has caused physiological resistance and adverse environmental effects. Long-term exposure to synthetic insecticides can cause irritation, severe allergic dermatitis, nausea, vomiting, headaches, and other CNS problems. Because of the development of resistance, cross-resistance, and probable toxicity problems connected with synthetic pesticides, as well as their increased expense, interest in plant-based solutions has resurfaced in recent years. Because of these circumstances, the effectiveness of 8, 11, 14-eicosatrienoic acid from Gliricidia sepium in mosquito control was investigated and found to be very effective. The newly discovered phytochemical's effect on non-target organisms was also investigated, and it was discovered to be non-toxic.